2014
DOI: 10.1371/journal.pone.0093688
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Mu Opioid Receptors Sensitizes Transient Receptor Potential Vanilloid Type 1 (TRPV1) via β-Arrestin-2-Mediated Cross-Talk

Abstract: The transient receptor potential family V1 channel (TRPV1) is activated by multiple stimuli, including capsaicin, acid, endovanilloids, and heat (>42C). Post-translational modifications to TRPV1 result in dynamic changes to the sensitivity of receptor activation. We have previously demonstrated that β-arrestin2 actively participates in a scaffolding mechanism to inhibit TRPV1 phosphorylation, thereby reducing TRPV1 sensitivity. In this study, we evaluated the effect of β-arrestin2 sequestration by G-protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 59 publications
0
51
1
Order By: Relevance
“…In this case, different barr2 dissociation profiles correlated with divergent positioning of the receptor C terminus with respect to the Gbg dimer, in which SNC80, the ligand that induced the more stable interaction between DOPr and barr2, also promoted barr2 association to Gbg locking all interaction partners within a stable complex (Audet et al, 2012). Recent studies indicated that stable interaction between barrs and opioid receptors may lead to the sensitization of TRPV1 signaling (Rowan et al, 2014a). The fact that this effect was associated with the administration of SNC80 but not ARM100390 (Rowan et al, 2014b) was interpreted as an indication that SNC80-occupied DOPrs could release TRPV1 signaling by acting as a scavengers for barrs that are otherwise constitutively associated with the channel.…”
Section: B D-opioid Receptor-b-arrestin Interactionmentioning
confidence: 89%
“…In this case, different barr2 dissociation profiles correlated with divergent positioning of the receptor C terminus with respect to the Gbg dimer, in which SNC80, the ligand that induced the more stable interaction between DOPr and barr2, also promoted barr2 association to Gbg locking all interaction partners within a stable complex (Audet et al, 2012). Recent studies indicated that stable interaction between barrs and opioid receptors may lead to the sensitization of TRPV1 signaling (Rowan et al, 2014a). The fact that this effect was associated with the administration of SNC80 but not ARM100390 (Rowan et al, 2014b) was interpreted as an indication that SNC80-occupied DOPrs could release TRPV1 signaling by acting as a scavengers for barrs that are otherwise constitutively associated with the channel.…”
Section: B D-opioid Receptor-b-arrestin Interactionmentioning
confidence: 89%
“…11 MOR agonists, such as morphine and DAMGO, sequester β-arrestin2, reduce TRPV1/β-arrestin2 interactions and increase TRPV1 activity in peripheral sensory neurons. 30 Previous studies showed that endogenous β-arrestin2 is required for the development of morphine tolerance, 80,81 and mice lacking β-arrestin2 demonstrate increased sensitivity to the antinociceptive effects of morphine. 82 Furthermore, hyperalgesia may rebound due to overactive PKA and result in phosphorylation and sensitization of TRPV1 during the process of patients ceasing opioid therapy.…”
Section: Mor Sensitizes Trpv1 Via β-Arrestin2mentioning
confidence: 99%
“…21 Current evidence emphasizes the importance of TRPV1 in morphine tolerance, dependence and morphine-induced antinociception. 10,29,30 Here, we review the current knowledge concerning these phenomena, focusing on morphine-induced TRPV1 activation. Furthermore, we highlight evidence characterizing downstream TRPV1 signaling molecules and their role in morphine tolerance, dependence and morphine-induced antinociception (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The four members of the arrestin protein family include arrestin-1 and -4 of visual sensory tissue and the nonvisual ubiquitously expressed arrestin-2 and -3, otherwise known as b-arrestin-1 and b-arrestin-2. Initially named for their capacity to prevent continued signaling of b-adrenergic receptors, b-arrestins are now known to regulate multiple GPCRs and TRP channels in the pain pathway (Rowan et al, 2014). The association of b-arrestins with GPCRs is facilitated by receptor phosphorylation, where agonist-occupied GPCRs are phosphorylated by a family of G protein-coupled receptor kinases (GRKs), in addition to PKC and PKA, which enhances association with b-arrestins.…”
Section: Kinase Scaffold Proteinsmentioning
confidence: 99%
“…This process may also contribute to endocannabinoid-and opioid-dependent downregulation of TRPV1-dependent pain . Conversely, chronic opioidinduced hyperalgesia was recently investigated, and evidence suggests that stimulation of the m-opioid receptor with agonists that cause robust receptor internalization enhance TRPV1 activity due to a loss of TRPV1-arrestin interactions (Rowan et al, 2014). Similarly, angiotensin 1R signaling in HEK-293 and vascular smooth muscle cells promotes TRPV4 internalization through an arrestindependent mechanism (Shukla et al, 2010).…”
Section: Kinase Scaffold Proteinsmentioning
confidence: 99%